2020
DOI: 10.1038/s41598-020-71629-z
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular clusterin expression is increased in diabetic nephropathy and protects against oxidative stress-induced apoptosis in podocytes

Abstract: Clusterin, a glycoprotein encoded by the CLU gene, is expressed in many tissues, including the kidney, and clusterin expression is upregulated in the glomeruli of patients with various forms of kidney disease. Here, we investigated the role of clusterin in diabetic nephropathy (DN). In this study, we found that glomerular clusterin expression was increased in both patients with DN and streptozotocin-induced diabetic mice and that it co-localised with the podocyte marker WT1, indicating clusterin is expressed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…We found that VSIG4 expression was higher in DN renal samples and was negatively correlated with GFR (P < 0:001, r = -0:783). CLU is a kind of complement regulatory protein which can bind to C5b-7 and inhibit the generation of membrane attack complex [59] and was found upregulated in the glomerular of both DN patients and streptozotocin-induced diabetic mice [46]. We found that CLU expression was higher in DN renal samples and was negatively correlated with GFR (P = 0:001, r = -0:639).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…We found that VSIG4 expression was higher in DN renal samples and was negatively correlated with GFR (P < 0:001, r = -0:783). CLU is a kind of complement regulatory protein which can bind to C5b-7 and inhibit the generation of membrane attack complex [59] and was found upregulated in the glomerular of both DN patients and streptozotocin-induced diabetic mice [46]. We found that CLU expression was higher in DN renal samples and was negatively correlated with GFR (P = 0:001, r = -0:639).…”
Section: Discussionmentioning
confidence: 69%
“…The GO enrichment analysis revealed that hub genes were involved in multiple biological processes, including regulation of complement activation, regulation of humoral immune response, humoral immune response, complement activation, regulation of immune effector process, and macrophage activation. The hub genes, such as C1QA, C1QB, C3, CFB, ITGB2, VSIG4, and CLU, can participate in complement cascade [44][45][46][47]. CD163, CD44, CD48, CD52, and CD53 may involve in humoral immune response and macrophage activation [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…We found that COL1A2 expression was upregulatedin DN renal tissues, was negatively correlated with GFR (P = 0:017, r = -0:800), and was positively correlated with Scr (P = 0:010, r = 0:607).CLUis a glycoprotein that is expressed in many tissues, including the kidney [59]. He et al found that glomerular CLU is upregulated in both patients with DN and streptozotocin-induced diabetic mice, and overexpressing CLU may protect against oxidative stress-induced apoptosis in podocytes [60]. Moreover, CLU may delay or even halt the progression of DN by modulating Akt-related pathways [61,62].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated that CLU has a cytoprotective role against the deleterious effects of oxidants, working as an antioxidant protein [ 53 ]. Recently, it was observed that glomerular CLU is upregulated in diabetic nephropathy and may have a protective effect against oxidative stress-induced apoptosis in podocytes [ 54 ]. Induction of CLU during IRI was proposed as a survival function in response to high levels of oxidative stress through a mechanism involved in survival autophagy [ 55 ].…”
Section: Discussionmentioning
confidence: 99%